Stigmatising beliefs about Alzheimer's disease: Findings from the Asian American Quality of Life Survey. (22nd October 2020) - Liang, Jiaming; Jang, Yuri; Aranda, María P.
Abstract: Responding to the public health significance of Alzheimer's Disease (AD) and lack of information on AD‐related issues in Asian Americans, the present study examined the prevalence and predictors of three stigmatising beliefs about AD (beliefs that associate AD with a normal process of ageing, family embarrassment and social avoidance) using a sample of Asian Americans representing diverse ethnic groups (Chinese, Asian Indian, Korean, Vietnamese, Filipino and other Asians) and a broad age range (18–98). Guided by the Sociocultural Health Belief Model, multivariate regression models of stigmatising beliefs about AD examined the effect of demographic characteristics (age, gender, marital status, education and ethnicity) and immigration and culture‐related variables (proportion of life in the U.S., English proficiency and acculturation). Data came from the 2015 Asian American Quality of Life survey ( N = 2, 609). Results indicate that the prevalence of stigmatising beliefs about AD varied across ethnicities. More than 63% of Vietnamese associated AD with a normal process of ageing, and about 10% of Chinese reported that they would feel embarrassed if their family member had AD. Logistic regression analyses demonstrated that advanced age, male gender, low education and limited English proficiency increased the odds of reporting one or more stigmatising beliefs about AD. The findings suggest varying degrees of AD‐related misconceptions and stigmatisation and call attention to the need for culturally sensitive AD education in Asian communities.